OPPORTUNITIES FOR THE USE OF INNOVATIVE TECHNOLOGIES IN THE ORGANIZATION OF INDEPENDENT EDUCATION IN THE CREDIT-MODULE SYSTEM (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
Any great events carried out in the history of mankind are directly embodied in Zamiri in harmony with science, technology and production technology.